Review of gastric cancer risk factors in patients with common variable immunodeficiency disorders, resulting in a proposal for a surveillance programme - Dhalla, F; da Silva, S; Lucas, M; Travis, S; Chapel, H (2011)
Common variable immunodeficiency disorders (CVIDs) are the most frequent symptomatic primary immunodeficiencies in adults. They comprise a heterogeneous group of pathologies, with frequent non-infectious complications in addition to the bacterial infections that usually characterize their presentation. Complications include a high risk of malignancy, especially lymphoma and gastric cancer. Helicobacter pylori infection and pernicious anaemia are risk predictors for gastric cancer in the general population and probably in patients with CVIDs. Screening for gastric cancer in a high-risk population appears to improve survival. Given the increased risk of gastric cancer in patients with CVIDs and prompted by a case of advanced gastric malignancy in a patient with a CVID and concomitant pernicious anaemia, we performed a review of the literature for gastric cancer and conducted a cohort study of gastric pathology in 116 patients with CVIDs under long-term follow-up in Oxford. Regardless of the presence of pernicious anaemia or H. pylori infection, patients with CVIDs have a 10-fold increased risk of gastric cancer and are therefore a high-risk population. Although endoscopic screening of all patients with CVIDs could be considered, a more selective approach is appropriate and we propose a surveillance protocol that should reduce modifiable risk factors such as H. pylori, in order to improve the management of patients with CVIDs at risk of gastric malignancy. © 2011 The Authors; Clinical and Experimental Immunology © 2011 British Society for Immunology.